2017
DOI: 10.1111/pedi.12622
|View full text |Cite
|
Sign up to set email alerts
|

No change in type 2 diabetes prevalence in children and adolescents over 10 years: Update of a population-based survey in South Germany

Abstract: Objective of this study was to analyze prevalence changes in type 2 diabetes (T2D) among children and adolescents over the last 10 years. We performed a cross-sectional survey in Baden-Württemberg (BW), Germany, by using a written questionnaire and comparing these results with T2D prevalence data from the same area retrieved in 2004/2005. In 2016, 50 patients with T2D under 20 years of age were registered in BW, Germany, which corresponds to a prevalence rate of 2.42 per 100 000 (95% confidence interval [CI]: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 12 publications
0
21
1
1
Order By: Relevance
“…Individuals diagnosed before 6 months of age now tend to be routinely investigated for monogenic forms of the disease [28], but the number of such cases is very small. Findings in the literature on whether or not type 2 diabetes is becoming more common in children and adolescents are inconsistent [29][30][31], but the distinction between the two types of diabetes is generally not difficult in the paediatric age group. Furthermore, European studies [30][31][32][33] confirm that the rate of type 2 diabetes is a small fraction of that of type 1 diabetes, and we do not therefore feel that misclassification of type 2 diabetes represents a serious challenge to the validity of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals diagnosed before 6 months of age now tend to be routinely investigated for monogenic forms of the disease [28], but the number of such cases is very small. Findings in the literature on whether or not type 2 diabetes is becoming more common in children and adolescents are inconsistent [29][30][31], but the distinction between the two types of diabetes is generally not difficult in the paediatric age group. Furthermore, European studies [30][31][32][33] confirm that the rate of type 2 diabetes is a small fraction of that of type 1 diabetes, and we do not therefore feel that misclassification of type 2 diabetes represents a serious challenge to the validity of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, while it is projected that by 2050 there may be a fourfold increase in the prevalence of youth‐onset T2DM in the United States, in a recent follow‐up survey of a cross‐sectional study, Neu et al . reported that the prevalence of youth‐onset T2DM in Germany remained stable over the past 10 years, and that the majority of youth‐onset T2DM cases were part of specific ethnic minorities (). Given the asymptomatic nature at T2DM followed by rapid progression with beta‐cell function deteriorating by 15–20% per year when diagnosed in young people and complications arising within 5 years, identification of individuals at high risk is crucial .…”
Section: Discussionmentioning
confidence: 99%
“…reported that the prevalence of youth-onset T2DM in Germany remained stable over the past 10 years, and that the majority of youth-onset T2DM cases were part of specific ethnic minorities ( 26,27 ). Given the asymptomatic nature at T2DM followed by rapid progression with beta-cell function deteriorating by 15-20% per year when diagnosed in young people and complications arising within 5 years, identification of individuals at high risk is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany specialized hospitals offer in-patient rehabilitation following the National Guidelines set by the AWMF (S2-Leitlinie [7]) and the Leitlinien der Deutschen Diabetes-Gesellschaft (DDG) [12]. Average rehabilitation has a duration of four weeks.…”
Section: In-patient Rehabilitation In Germanymentioning
confidence: 99%